Determining the yield stress of a Biopolymer-bound Soil Composite for extrusion-based 3D printing applications. (25th October 2021) - Biggerstaff, Adrian; Fuller, Gerald; Lepech, Michael; Loftus, David
Highlights: Yield stress measurements of Biopolymer-bound Soil Composite (BSC) were conducted. Models were developed to predict the static and dynamic yield stress of BSC mixtures. A 3D printable range of BSC mixtures was identified based on soil volume fraction. Abstract: Biopolymer-bound Soil Composite (BSC) is a novel class of construction materials with potential use in extraterrestrial infrastructure development and more sustainable construction on Earth. Little is known about the rheological properties of this new material and its suitability for extrusion-based 3D printing (E3DP). This paper presents methods for testing BSC yield stress and proposes hydrodynamic and frictional yield stress models for predicting the static and dynamic yield stress of BSC mixtures. Using experimental results, a soil volume fraction range for BSC is identified that may be suitable for E3DP based on extrudability and shape stability requirements.